Mnemonic Techniques in Slow Learner Student Learning in Elementary School - Marlina Eliyanti Simbolon; Fridolin Vrosansen Borolla; Mega Prasrihamni; Asep Supena (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to identify various kinds of mnemonic techniques found in the literature study. This type of research uses a qualitative research type with a literature review type. This study analyzes twenty journal articles both nationally and internationally by searching from google scholar whose research results found the six highest mnemonic, the results include slow learners, namely acronyms, acrobatics (first letter), chungking, loci, rhyme and keywords. The purpose of the mnemonic technique is to help teachers in teaching students in elementary schools in the process of remembering and understanding learning.